1981
DOI: 10.1172/jci110277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin II on uterine and systemic vasculature in pregnant sheep.

Abstract: A B S T R A C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
1
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 17 publications
9
70
1
1
Order By: Relevance
“…Inasmuch as there were significant agedependent changes in MAP and HR, analysis of the absolute values might miss important changes in the responses to ANG II. Therefore, the data were further analyzed using the relative change from baseline (%⌬), which takes into account the changes in baseline values and permits a comparison across ages and between hemodynamic parameters (32). At each study period, systemic i.v.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inasmuch as there were significant agedependent changes in MAP and HR, analysis of the absolute values might miss important changes in the responses to ANG II. Therefore, the data were further analyzed using the relative change from baseline (%⌬), which takes into account the changes in baseline values and permits a comparison across ages and between hemodynamic parameters (32). At each study period, systemic i.v.…”
Section: Resultsmentioning
confidence: 99%
“…In what may be an analogous situation, the adult uterine vascular bed predominantly expresses AT 2 in the VSM (21,23). It also demonstrates dose-dependent increases in vascular resistance during systemic ANG II infusions that are less than systemic responses (21,32). Furthermore, as seen in the neonatal hindlimb, it too is unresponsive to intra-arterial ANG II infusions until there is evidence that the peptide has spilled over into the systemic circulation (56).…”
Section: Peripheral Effects Of Ang II After Birthmentioning
confidence: 99%
“…Experiments in primates have shown that the infusion of low-dose Ang II may actually increase uterine blood flow. 37 Rosenfeld et al 38 have shown that the low-dose infusion of Ang II has minimum effect on the uterine blood flow but that the pharmacological-dose (10 g/min) infusion decreases uterine blood flow in gravid ewes. For prorenin to participate in the regulation of blood flow, it must be available locally in a biologically active form.…”
Section: Discussionmentioning
confidence: 99%
“…1A). Since there were age-dependent changes in basal hemodynamic parameters, the data were analyzed using the relative change from baseline (%⌬), which permits a comparison across ages and between hemodynamic variables (21,29). Although there were age-dependent differences in basal MAP and HR, there were no differences in baseline measurements obtained immediately before each dose of PE (p Ͼ 0.05, ANOVA) at each age.…”
Section: Resultsmentioning
confidence: 99%
“…To compare responses by hemodynamic parameters with different units, e.g. MAP, FmBF, and FmVR, and changes across postnatal age, data are presented as the relative or percentage change (%⌬) from baseline (21,29). One-way ANOVA for repeated measures was used to analyze the changes in hemodynamic parameters across postnatal ages and across doses within each age group.…”
Section: Methodsmentioning
confidence: 99%